2017
DOI: 10.1186/s12974-017-0860-3
|View full text |Cite
|
Sign up to set email alerts
|

The PD-1: PD-L1 pathway promotes development of brain-resident memory T cells following acute viral encephalitis

Abstract: BackgroundPrevious work from our laboratory has demonstrated that during acute viral brain infection, glial cells modulate antiviral T cell effector responses through the PD-1: PD-L1 pathway, thereby limiting the deleterious consequences of unrestrained neuroinflammation. Here, we evaluated the PD-1: PD-L1 pathway in development of brain-resident memory T cells (bTRM) following murine cytomegalovirus (MCMV) infection.MethodsFlow cytometric analysis of immune cells was performed at 7, 14, and 30 days post-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 60 publications
4
73
0
Order By: Relevance
“…Previous findings from our laboratory reported that CD103 þ CD69 þ CD8 þ T-cells persist within the brain of murine cytomegalovirus (MCMV)-infected animals. We also reported that PD-1: PD-L1 signaling altered expression CD103 and CD69 [10]. There is also evidence that PD-L1 expression on microglia regulates the differentiation of Th1 cells via nitric oxide, suggesting a role for these cells in regulating T-cells [2].…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Previous findings from our laboratory reported that CD103 þ CD69 þ CD8 þ T-cells persist within the brain of murine cytomegalovirus (MCMV)-infected animals. We also reported that PD-1: PD-L1 signaling altered expression CD103 and CD69 [10]. There is also evidence that PD-L1 expression on microglia regulates the differentiation of Th1 cells via nitric oxide, suggesting a role for these cells in regulating T-cells [2].…”
Section: Introductionsupporting
confidence: 52%
“…In our previous study, we used a well‐established mouse model of MCMV brain infection to demonstrate a role for the PD‐1: PD‐L1 pathway in development of CD103 + CD69 + CD8 + bT RM populations in vivo following acute viral infection . Here, we followed‐up on those findings by first demonstrating that some of the bT RM were specific for a previously identified viral T‐cell epitope .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Many additional signals are central in differentiation and survival of T RM cells, for example TGF-β, IL-15, TNF-α and IL-33 (Mackay et al, 2013, Skon et al, 2013). Upon intracerebral infection of adult mice the PD-1/PDL-1 pathway seems to contribute to the generation of CD8 + T RM cells (Prasad et al, 2017). It will be of interest to investigate whether and how these signals contribute to the establishment of T RM cells upon MCMV infection of newborn mice, especially taking into account the immaturity of the immune system, the developmental changes that occur simultaneously and disparate cytokine milieu in newborn mice as compared to adult animals.…”
Section: Discussionmentioning
confidence: 99%